Kampung Sampah Bernilai (SALAI) Sebagai Upaya Pemberdayaan Masyarakat di Kelurahan Sempaja Timur Kota Samarinda - Regina, Putry; ., Saraka; Wahyuni, Sri (Equilibrium: Jurnal Pendidikan, 2024)
Abstract. This research aims to analyze the awareness stage, capacity building stage, empowerment stage and to describe the factors that support and inhibit community empowerment. The research was carried out at RT 43, Sempaja Timur Subdistrict, with SALAI village administrators, empowerment facilitators, and the community of SALAI RT 43 village. This research used qualitative research methods and used observation, interview and documentation study techniques. Data analysis techniques are carried out by data reduction, data presentation, and drawing conclusions. The results of research on Community Empowerment through the Valued Waste Village Program (SALAI), namely the awareness stage which is carried out by identifying needs and socializing the program to the community, the capacity building stage which is carried out by providing capacity through training programs, the empowerment stage is carried out by giving the community greater opportunities to take responsibility responsible for program sustainability. The supporting factors in community empowerment are community motivation and government policy, while the inhibiting factors in implementing the valuable waste village program are infrastructure.